Newborn screening in Nigeria: will incorporating congenital hypothyroidism with sickle cell disease improve neonatal screening programme? SCD and CH combined screening - Yarhere, Iroro Enameguolo; Jaja, Tamunopriye; Briggs, Datonye; Iughetti, Lorenzo (Acta Biomedica Atenei Parmensis, 2019)
ntroduction: Nigeria like many African countries has tried to start the newborn screening for congenital hypothyroidism and many failed. Since sickle cell disease is more common in Nigeria, the hypothesis is that incorporating it into a screening programme for congenital hypothyroidism will improve the uptake of the programme by parents and government. Methods: Different aspects of newborn screening with difficulties and challenges in running newborn screening were identified and discussed. Result: Identifying that for newborn screening to be successful, several key factors have to be put in place including but not limited to organizational structure, system thinking, finance, legislative and political will. A proper recall system for test positives and diagnostic/confirmatory test must be put in place before the programme starts. Since several other screening programmes like sickle cell disease, cervical and breast cancer have run successfully in Nigeria, incorporating one of them into the newborn screening for CH can make the programme succeed as there will be better uptake by the population and the policy makers. Conclusion: The difficulty in establishing a newborn screening programme in Nigeria stem from health care financing, organizing the programme from screening through to recall and treatment, and ultimately, prevention of diseases.